Strategi Pemasaran Tanaman Hias “Bunga Ditepi Jalan” Di Kelurahan Winangun Satu Kecamatan Malalayang Kota Manado - Paendong, Eunike Louisa; Porajow, Oktavianus; Benu, Noortje Marselianie (AGRI-SOSIOEKONOMI, 2023)
The aim of this research is to find out what factors exist in the internal and external environment and to determine the right marketing strategy for the "Bunga Ditepi Jalan" ornamental plant business located in Winangun Satu Village, Malalayang District, Manado City. The research was conducted from October to November 2022, taking place in the Winangun Satu Village, Malalayang District, Manado City. The data collected is the collection of primary data obtained by conducting direct interviews using a questionnaire to the owner of the ornamental plant business "Bunga Ditepi Jalan" and consumers. The research sample was taken from 13 respondents concerned to fill out the research questionnaire. SWOT analysis has 4 (four) stages, namely data collection, SWOT determination, strategy formulation and decision making as well as business positioning. Based on the SWOT analysis that has been carried out, it shows that the ornamental plant business "Bunga Ditepi Jalan" is in Quadrant I with a score of (1.1:0.8) which means that the business is in a very profitable situation. This market has opportunities and strengths so that it can make the best use of the opportunities that exist. The right marketing strategy is the SO strategy, namely maintaining the quality and variety of ornamental plants, expanding online promotions, taking advantage of market opportunities and selling at affordable prices and expanding markets outside the region.